A Facile Route to Bimetal and Nitrogen‐Codoped 3D Porous Graphitic Carbon Networks for Efficient Oxygen Reduction. Issue 31 (7th July 2016) - Zhang, Zhengping; Dou, Meiling; Liu, Haijing; Dai, Liming; Wang, Feng
Abstract : Bimetal nitrogen‐doped carbon with both Fe and Co, derived from the pyrolysis carbon of iron and cobalt phthalocyanine‐based conjugated polymer networks, possesses a few‐layer graphene‐like texture with hierarchical porosity in meso/micro multimodal pore size distribution. The novel electrocatalyst exhibits Pt‐like catalytic activity and much higher catalytic durability for oxygen reduction.